Pengaruh Terapi Aktivitas Bermain Mewarnai Terhadap Tingkat Kecemasan Anak dirawat inap RSUD Kabupaten Tangerang - Rianti; Ria Setia Sari; Alif fuadi (Jurnal Kesehatan, 2022)
One of the ways to overcome anxiety is to play. In children, playing is a daily activity that they always do, so playing is a suitable means as a therapy to reduce anxiety in children. One of the games that can be done for children is coloring play therapy. The purpose of this study was to determine the effect of coloring play activity therapy on the level of anxiety in children hospitalized at Tangerang District Hospital. The type of research used is quantitative research with Pre Experimental Design research design and One-Group Pretest-Posttest Design research design. The instrument used is a questionnaire and the analytical test used is the Wilcoxon Signed Ranks Test. The results in this study are the value of Sig. = 0.004 on the anxiety level variable. So it can be concluded "Ha is accepted" (Sig 0.004 < 0.05), meaning that there is an effect of coloring play activity therapy on the value of the anxiety level of children hospitalized in Tangerang District Hospital..